We Conquared all of Europe : Red Odyssey II - Goulding, Jeff (Sussex : Pitch Publishing, 2019)
We Conquered All of Europe: Red Odyssey II charts the re-emergence of Liverpool FC as one of European football's most feared teams. Jeff Goulding chronicles the whole journey through the eyes of the supporters, also including key insights from former players and eyewitness accounts of the most incredible moments of the Jurgen Klopp era.
Keywords: Liverpool Football Club -- History; Liverpool Football Club; Soccer teams